The Influence Of Lifestyle And Customer Experience On Purchasing Decision Brand Handphone Iphone (Survey on iPhone Brand Mobile Phone Users at Tasikmalaya City) - Dewi Sri Rahayu; Ari Arisman; Depy Muhamad Pauzy (Journal of Indonesian Management, 2023)
This purpose of this study to determine the influence of lifestyle and customer experience on purchasing decision brand handphone iPhone (Survey on iPhone Brand mobile Phone users at Tasikmalaya City). The method used is a quantitative method with a research sample of 100 respondents who are a iPhone mobile users at Tasikmalaya City. The data is used primary data and secondary data. The analitytical tool in this research is multiple regression using by SPSS version 25. The result showed that simultaneously lifestyle and customer experience has a significant influence on purchasing decision. Partially lifestyle has negative and unsignificant influence on purchasing decision. Partially customer experience has positive and significant on purchasing decision.